Maximal subgroups of finite groups - S. Srinivasan (International Journal of Mathematics and Mathematical Sciences, 1990)
In finite groups maximal subgroups play a very important role. Results in the literature show that if the maximal subgroup has a very small index in the whole group then it influences the structure of the group itself. In this paper we study the case when the index of the maximal subgroups of the groups have a special type of relation with the Fitting subgroup of the group.